Corticosteroid injection for the treatment of carpal tunnel syndrome. Issue 11 (1st November 2000) - O'Gradaigh, D; Merry, P
Abstract : OBJECTIVE: To compare low and high dose, and short and long acting corticosteroids in the treatment of carpal tunnel syndrome. METHODS: A randomised, controlled, single blind trial with electromyographic and subjective outcome measures. RESULTS: 25 mg hydrocortisone is as effective as higher doses or long acting triamcinolone at a six week and six month follow up. CONCLUSION: As low dose steroid is as effective, and potentially less toxic, this should be the recommended dose for injection of carpal tunnel syndrome.